2022
DOI: 10.3390/molecules27041346
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS-Mediated Metabolic and Cytotoxic Effects of Isoproterenol on Cardiomyocytes Are p53-Dependent and Reversed by Curcumin

Abstract: Acute β-adrenergic stimulation contributes to heart failure. Here, we investigated the role of p53 in isoproterenol (ISO)-mediated metabolic and oxidative stress effects on cardiomyocytes and explored the direct protective effects offered by the antioxidant nutraceutical curcumin. Differentiated H9C2 rat cardiomyocytes treated with ISO were assayed for glucose uptake, lactate release, and mitochondrial reactive oxygen species (ROS) generation. Survival was assessed by sulforhodamine B assays. Cardiomyocytes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“… 54 Interestingly, the cells treated with NCF maintained ΔΨm and limited mitochondrial p53 accumulation compared to hypoxic control cells. Our finding agrees with a previous study that reported that nanocurcumin treatment inhibits p53 mitochondrial translocation in primary human ventricular cardiomyocytes under hypoxic stress 30,55 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“… 54 Interestingly, the cells treated with NCF maintained ΔΨm and limited mitochondrial p53 accumulation compared to hypoxic control cells. Our finding agrees with a previous study that reported that nanocurcumin treatment inhibits p53 mitochondrial translocation in primary human ventricular cardiomyocytes under hypoxic stress 30,55 …”
Section: Discussionsupporting
confidence: 94%
“…Our finding agrees with a previous study that reported that nanocurcumin treatment inhibits p53 mitochondrial translocation in primary human ventricular cardiomyocytes under hypoxic stress. 30,55 Hypoxic stress causes a dramatic increase in oxidative stress markers, that is, free radical generation, NO production, and iNOS expression, in C2C12 myoblasts. These findings demonstrate an increase in oxidative stress, which triggers the accumulation of AOPP, resulting in cellular stress in response to hypoxic insult.…”
Section: Discussionmentioning
confidence: 99%
“…5A and B) highlighted that while ROS-driven TP53 activation significantly affects cardiomyocyte hypertrophy and apoptosis monotonically, reactions regulating ROS generation and scavenging exhibited nonlinear, variable impacts on the cardiomyocyte phenotype. Prior research suggests that ROS-mediated TP53 activation can drive cardiomyocyte metabolic remodeling [72] and transition from adaptive cardiac hypertrophy to maladaptive cardiac dysfunction via pro-apoptotic and anti-angiogenesis functions of TP53 [47]. Our context-specific analysis highlighted considerable variability in reactions at both upstream (e.g., NOX4 => ROS) and downstream of ROS (e.g., ROS => CaMK) across different HCM mutations and species (refer to Fig.…”
Section: Discussionmentioning
confidence: 84%
“…It is a nonselective β-receptor agonist and is frequently used in intervention trails to induce ischemia and infarction of myocardium 11 . Being β-receptor agonist, it is positive ionotropic as well as chronotropic on myocardium that increase workload thus oxygen demand of myocardium 12,13 . This ultimately leads to ischemia and infarction.…”
Section: Discussionmentioning
confidence: 99%